Recognizing socially shared regulation by using the temporal sequences of online chat and logs in CSCL. (April 2016) - Järvelä, Sanna; Malmberg, Jonna; Koivuniemi, Marika
Abstract: The increasing amount of empirical research shows that the role of regulatory processes is critical in CSCL and collaborative learning settings. However, the current conceptual definitions and specificity of the findings vary. This is most probably because of limitations in the methods investigating regulated learning in a collaborative learning context. This study aimed to provide empirical evidence for how self- and shared regulation activities are used and whether they are useful for collaborative learning outcomes. Eighteen graduate students worked in collaborative groups for seven weeks in a CSCL course and the data of this study focuses on three one week online collaborative learning phases in the course. Temporal and sequential analysis of chat discussions and log file traces were matched to find evidence about whether the students' collaboratively planned regulatory activities became shared in practice. The results show evidence that collaborative planned regulatory activities become shared in practice. The groups that achieved good learning results used multiple regulatory processes to support their learning and also reached shared regulation. The four microlevel examples demonstrate simplified patterns of the activation of self-regulation and shared regulation. In conclusion, individual socially shared regulation plays a critical role in successful collaborative learning. Highlights: Temporal and sequential analysis of chat discussions and log file traces are used. The results show that collaborative planned regulatory activities become shared in practice. Use of multiple regulatory processes and shared regulation contributed to learning results. Microlevel examples demonstrate simplified patterns of SRL and shared regulation. Shared regulation plays a critical role in successful collaboration.